Advancing sustainable development goals through interdisciplinarity in sustainable tourism research. Issue 3 (4th March 2023) - Nunkoo, Robin; Sharma, Anuj; Rana, Nripendra P.; Dwivedi, Yogesh K.; Sunnassee, Vivek A
Abstract: The sustainable development goals (SDGs) address multifaceted problems that lie at the intersection between natural and socio-economic systems. While scholars agree that interdisciplinary research is needed to advance the SDGs, the concept of interdisciplinarity itself has been given limited attention. This article explores the interdisciplinarity of research published in the Journal of Sustainable Tourism using references cited by the journal's articles. We use structural topic modeling to analyze research trends. The findings suggest that the research has become more interdisciplinary, however, knowledge is defined primarily by tourism studies and the business management discipline. To advance the SDGs, researchers should engage with disciplines such as anthropology and the humanities that can bring critical issues such as power relations and socio-cultural values to the forefront of sustainability discourses. Research should also conceptualize the SDGs as a network of targets to facilitate the integration of sustainable tourism outcomes with broader development goals.